Investigating the Impact of Information Technology, Absorptive Capacity, and Dynamic Capabilities on Firm Performance: An Empirical Study. (November 2021) - Ma, FeCheng; Khan, Farhan; Khan, Kashif Ullah; XiangYun, Si
In today's dynamic market environment, information technology (IT) enables firms to obtain knowledge they need to achieve superior performance. To this end, the present study explores the effects of IT, absorptive capacity (ACAP), and dynamic capabilities (DCs) on firm performance (FP) by employing empirical research design. In addition, the study focuses on the DCs perspective and ACAP as a firm knowledge-based view focusing on those firms where technology involved in either a particular unit of the firm or as a whole in operational processes. The data (total 241) was analyzed through AMOS, a mathematical analysis methodology focused on structural equation modeling (SEM). Moreover, through Sobel test we further verify the indirect impact of IT on FP.